The practical realities of Mobile Robotic Telepresence: understanding experiences, interactions and the implications for use in organisational spaces - Boudouraki, Andriana (2024)
This thesis presents an in-depth examination of Mobile Robotic Telepresence (MRP). The work uncovers the social organisation of interactions and highlights the practical considerations of using the technology in organisational spaces. MRP systems are remotely controlled, mobile robots with video-conferencing capabilities. A remote user can drive the robot from an online interface whilst projecting their face on the robot’s screen. Thus the remote user is (in theory) able to move independently.